Aspek Ekonomi dan Sosial - Devi Tri Saputri Manik; Nurul Fazira Nasution; Siska Safitri (Journal of Management and Creative Business, 2025)
This journal focuses on the interaction between economic conditions and social structures that influence the well-being of society, as well as the relationship between economic and social aspects and their impacts on communities. Socioeconomic components such as education, health, and employment are interconnected and affect the quality of life. The study identifies various issues that arise, including poverty, unemployment, and social inequality, all of which stem from injustices in the distribution of economic resources. The effects of these injustices can be observed in the rising unemployment rates and declining quality of life, which in turn affect the social and economic stability of communities. Additionally, economic barriers such as policy uncertainty, lack of infrastructure, and limited access to capital hinder economic growth. Many communities remain trapped in a cycle of poverty due to inadequate access to training and education. To promote economic growth and social welfare, the government must provide support through inclusive economic policies, social assistance programs, skills training, and investments in infrastructure. Effective solutions are expected to be found by understanding the relationship between economic and social aspects and the existing barriers.